Effect of macroeconomic variables on performance of agriculture firms - Reaz, Md (2017)
The impacts of macroeconomic variables over the years have gained the attention of not only scholars but also policy makers around the world. This is because the effect of macroeconomic variables increases the uncertainty over the time which makes it more difficult for international trade and investment decision, and financial performance as well. This study examines the effect of macroeconomic variables on agriculture firms in Malaysia by using system-GMM dynamic panel techniques and GARCH (1, 1) for the period of 2001 and 2015. The findings from GARCH (1,1) confirmed the volatility of Malaysian Ringgit; where the volatility follows over similar trend. The analysis result of system-GMM of dynamic panel data shows Malaysian Ringgit has a positive impact on the financial performance of agriculture firms in Malaysia and the results are in line with our hypothesis. On the other hand, macroeconomic variables of the study i.e Money Supply (MS), Interest Rate (IR), Gross Domestic Products (GDP) and Consumer Price Index (CPI) show mixed results in relation with the financial performance of Agriculture companies in Malaysia. All the macroeconomic variables seem to have a positive and significant relationship with ROA except for Consumer Price Index (CPI) and Interest Rate (IR). While CPI is the only variable this shows a negative association with ROE. On the other hand, for the farm level variables, namely, ARME and AVA show a positive impact on financial performance. This study contributes to the existing literature of the exchange rate volatility by looking at its effect precisely on agriculture businesses in Malaysia. Using system- GMM methods give novelty to the study. For the market players, Malaysian Agricultural farms can predict the possible movement of exchange rate; so that they can develop business policy to enhance financial performances. Also, farm level variables can help them to reconsider their business strategy to boost up business. Further, for government and policy makers study results provide a comprehensive insight on the co-movement of exchange rate with specified macro variables. Understanding such dynamics enables the government to predict substantially the trend and impact so that they may come up with preventive measures rather than wait and see what will happen. It is important to control the volatility on the exchange rate that is expected to attract foreign capital inflows. Moreover, this encourages local investors to boost aggregate investment, thus increases income, consumption and overall economy of the country.